Refugee Status in Saudi Arabia and How the Kingdom Apply some of the 1951 Convention Articles Regarding their Situation (The International Journal for Scientific Research, 2025)
This research aims to study the status of refugees in the Kingdom of Saudi Arabia by analyzing the legal, social, and economic dimensions that govern their status in the country. The research begins by explaining the concept of asylum in the Arabic language, and within the framework of international law and relevant agreements, such as the 1951 Convention relating to the Status of Refugees, which the Kingdom has not signed, but deals with asylum issues according to its internal policies and the humanitarian principles on which it is based. The research reviews how refugees enter the Kingdom of Saudi Arabia, their numbers, in addition to the policies followed in receiving them and providing their basic needs. The research relies on the descriptive analytical approach, as data is collected from various sources, including official reports, academic studies, and data from international organizations, and an analysis of local laws and regulations related to refugees. The status of refugees in the Kingdom is compared to international standards to understand similarities and differences and to evaluate the various impacts of this situation on refugees and the Kingdom. The research also discusses the rights that refugees obtain within the Kingdom, such as health care, education, work, freedom of movement, and the right to litigation. The research also focuses on the humanitarian role played by the Kingdom through hosting refugees and providing financial and relief assistance to humanitarian projects, whether inside the Kingdom or through supporting international relief initiatives.The results show that the Kingdom of Saudi Arabia provides significant support to refugees through humanitarian assistance and basic services, but it faces challenges related to their legal status. Despite this, Saudi Arabia remains a major player in providing humanitarian assistance locally and internationally. The situation requires improving legislative frameworks and internal policies to guarantee the rights of refugees facilitate their integration into Saudi society under international standards and enhance the Kingdom's role in humanitarian work.
Keywords: Refugees; Saudi Arabia; asylum; 1951 convention; Refugee rights; legal framework; Saudi humanitarian efforts; King Salman Humanitarian Aid and Relief Center